Photovoltaics-Driven Power Production Can Support Human Exploration on Mars - Abel, Anthony J.; Berliner, Aaron J.; Mirkovic, Mia; Collins, William D.; Arkin, Adam P.; Clark, Douglas S. (Frontiers in Astronomy and Space Sciences, 2022)
A central question surrounding possible human exploration of Mars is whether crewed missions can be supported by available technologies using in situ resources. Here, we show that photovoltaics-based power systems would be adequate and practical to sustain a crewed outpost for an extended period over a large fraction of the planet’s surface. Climate data were integrated into a radiative transfer model to predict spectrally-resolved solar flux across the Martian surface. This informed detailed balance calculations for solar cell devices that identified optimal bandgap combinations for maximizing production capacity over a Martian year. We then quantified power systems, manufacturing, and agricultural demands for a six-person mission, which revealed that photovoltaics-based power generation would require <10 t of carry-along mass, outperforming alternatives over 50% of Mars' surface.